The influence of ownership structure on transfer pricing - Purnamasari, Wiwid Aprilianingrum (Journal of Contemporary Accounting, 2020)
This research is to analyze the influence of ownership structure on transfer pricing. The ownership structure in this study consisted of foreign ownership, managerial ownership, institutional ownership, concentrated ownership, and government ownership. Purposive sampling was used to collect 148 manufacturing companies listed in the Indonesian Stock Exchange between 2013 and 2017 out of 694 samples using EViews-9 and a generalized linear model. The results showed that foreign ownership and government ownership had positive effects on transfer pricing. In contrast, managerial ownership, institutional ownership, and concentrated ownership negatively affected transfer pricing.